Byron
XIII, 262 p.
Keywords: This exciting collection represents a range of scholarly approaches and include close textual study, comparative readings, and broad cultural analysis. Contributors to this collection include Bernard Beatty, Peter Cochran, Marilyn Gaull, Charles E. Robinson, Andrew Stauffer, and Timothy Webb.